ADVANTAGES AND LIMITATIONS OF THE USE OF ACE INHIBITORS - Alibasic, Esad; Ljuca, Farid; Ramic, Enisa; Bajraktarevic, Amila; BaticMujanovic, Olivera; Dzafic, Fejzo; Zildzic, Muharem (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Analysis of advantages and limitations in the application of ACE inhibitors.Background: ACEI are most frequently used group of antihypertensives. The mechanism ofaction of ACEI is such an act who works on modulating the renin-angiotensin-aldosteronesystem (RAAS). By blocking the angiotensin converting enzyme, ACEI significantly block theconversion of angiotensin I to angiotensin II. At the same time, reduce the degradation ofbradykinin ACEI. Like any group of antihypertensive drugs, ACEI have some advantages andlimitations (eg. Tolerability, side effects, cost) that can be critical for a decision on theapplication in an individual patient. Application of ACEI has priority code: subclinical organdamage (left ventricular hypertrophy, asymptomatic atherosclerosis, microalbuminuria, renaldysfunction), clinical events (previous stroke, previous myocardial infarction, heart failure,recurrent atrial fibrillation, renal failure / proteinuria), certain conditions (metabolic syndrome,diabetes). Restrictions or possible side effects of ACEI are cough, hyperkalemia, headache,